Implementasi Sains Teknologi Engineering dan Matematika (STEM) berbasis kewirausahaan budidaya lele dumbo dengan media bioflok dan pakan Bungkil Inti Sawit (BIS) di SMP Purnama Pekanbaru - Yustina Yustina; Nursal Nursal; Indra Suharman; Arif Riandra; Oky Priawan; Winda Sari (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2019)
Community Service aims to determine the ability of students in the Implementation of Science Technology Engineering and Mathematics (STEM) Based on Entrepreneurship of Dumbo Catfish Cultivation with Bioflok and Feed Media made by Palm Kernel Oil (BIS). P2M activities are conducted at Pekanbaru Purnama Middle School through Extracurricular learning activities from March to June 2019. Participants are 20 students consisting of 4 groups. The method of using the STEM approach with the Project Based Learning (PjBL) model consists of 3 stages, namely: 1. Preparation: bioflok making training, feed making and seed procurement; 2. Implementation: treatment, maintenance, supervision and collection of growth data, operational costs: 3. Analysis of entrepreneurial economic data and STEM capabilities. Instrument for collecting growth data and operational costs using logbooks and observation sheets. Data on STEM and Entrepreneurship Capabilities using Student Worksheets. Data on fish growth and operational costs, then percentage, were scaled, tabulated and analyzed descriptively. The results of STEM abilities were obtained namely Science ability with a score of 80 (good category); Engineering 50 ability (less category), Technology ability with a score of 60 (sufficient category) and Mathematical ability with a score of 65 (sufficient category). Entrepreneurial economic analysis with a score of 75 (sufficient category) and 50% of participants get a profit of 30% from catfish production within 3 months.